Navigating Technological Frontiers: The Significance of Mixed Reality in Pre-service Teacher Curriculum in Nigeria - Vasudevan, Asokan; Lawal, Uthman Shehu; Mahmud, Binta; Salihu, Ibrahim; Hunitie, Mohammad Faleh Ahmmad; Mohammad, Suleiman Ibrahim Shelash (Journal of Ecohumanism, 2024)
Purpose: This paper explores the significance of integrating Mixed Reality (MR) technologies into pre-service teacher education programs in Nigeria. MR, which blends virtual and augmented realities, offers unique opportunities for educators to develop essential skills and enhance their pedagogical approaches. Theoretical Framework: This paper argues for including Mixed Reality (MR) in Nigerian teacher training. It uses TPACK theory to show how MR aligns with effective teaching and the SAMR model to assess how MR can be integrated for maximum impact. Method: Document analysis and secondary data were used in the study. In other words, the authors analyze existing research on mixed reality (MR) and teacher education to argue for the importance of integrating MR into pre-service teacher education programs in Nigeria. Results and Conclusion: Review revealed that MR allows pre-service teachers to virtually explore historical sites, manipulate 3D objects, and practice in simulated classrooms, fostering deeper understanding and engagement. Also, MR facilitates the application of theoretical concepts in simulated scenarios, preparing pre-service teachers for real-world classrooms. However, challenges exist such as, unequal access to reliable internet, power, and MR headsets impedes widespread implementation. The conclusion stresses the transformative potential of MR in preparing future educators for the evolving technological landscape. Research Implications: This review suggests that Mixed Reality has the potential to revolutionize pre-service teacher education in Nigeria by providing a more engaging, immersive, and effective learning experience. However, overcoming challenges related to access, training, and cultural context is crucial for successful implementation. Originality/Value: The article affirms the potential of MR as a tool for improving teacher education in developing countries.